Sporadic primary pulmonary hypertension is associated with germline mutations of the gene encoding BMPR-II, a receptor member of the TGF-β family. Issue 10 (1st October 2000) - Thomson, Jennifer R; Machado, Rajiv D; Pauciulo, Michael W; Morgan, Neil V; Humbert, Marc; Elliott, Greg C; Ward, Ken; Yacoub, Magdi; Mikhail, Ghada; Rogers, Paula; Newman, John; Wheeler, Lisa; et al.
Abstract : BACKGROUND: Primary pulmonary hypertension (PPH), resulting from occlusion of small pulmonary arteries, is a devastating condition. Mutations of the bone morphogenetic protein receptor type II gene ( BMPR2), a component of the transforming growth factor beta (TGF-β) family which plays a key role in cell growth, have recently been identified as causing familial PPH. We have searched for BMPR2 gene mutations in sporadic PPH patients to determine whether the same genetic defect underlies the more common form of the disorder. METHODS: We investigated 50 unrelated patients, with a clinical diagnosis of PPH and no identifiable family history of pulmonary hypertension, by direct sequencing of the entire coding region and intron/exon boundaries of the BMPR2 gene. DNA from available parent pairs (n=5) was used to assess the occurrence of spontaneous (de novo) mutations contributing to sporadic PPH. RESULTS: We found a total of 11 different heterozygous germline mutations of the BMPR2 gene in 13 of the 50 PPH patients studied, including missense (n=3), nonsense (n=3), and frameshift (n=5) mutations each predicted to alter the cell signalling response to specific ligands. Parental analysis showed three occurrences of paternal transmission and two of de novo mutation of the BMPR2 gene in sporadic PPH. CONCLUSION: The sporadic form of PPH is associated with germline mutations of the gene encoding the receptor protein BMPR-II in at least 26% of cases. A molecular classification of PPH, based upon the presence or absence of BMPR2 mutations, has important implications for patient management and screening of relatives.